Personality Career Test Android Mobile Application - Hamid, Suaidi; Norhalina Senan (Applied Information Technology And Computer Science, 2021)
The project Personality Career Test is about developing a mobile app that helps user to determine their personality and narrow down some of suggested types of career that suits the user personality. User will answer a personality test module that consists of 55 questions. At the end of the test, the app will calculate the user scores and present 3 keyword that represents the user personality. Based on the results, the app will give examples of careers that sought these types of personality. This app helps to improve personality tests interface appeal and accessibility that most schools are facing issue with the current paper-based method. This app will be available on all android devices. The application is built using unity as the main authoring tools and Adobe Illustrator to make assets to build the software. Multimedia Content Development (MMCD) methodology is used as the methodology to develop this application to narrow down system requirements and user requirements.